ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA VIII SMP PADA MATERI PERSAMAAN GARIS LURUS BERDASARKAN GENDER - Nenden Fatimah; Nelly Fitriani; Puji Nurfauziah (IKIP Siliwangi, 2023)
The purpose of this study is to identify and analyze the mathematical communication abilities of junior high school students in grade VIII.. In this study, a descriptive qualitative research type was used. The subject are 25 students in class VIII at SMP Negeri 36 Bandung, 13 of whom are female and 12 of whom are male.. The data collection technique is 3 questions in the form of descriptions, each of which represents an indicator of mathematical communication ability. The data processing technique is to analyze the mathematical communication ability of straight line equations in terms of gender in each indicator. Based on the results of the analysis, it was obtained that the average score of male students was 40.0% and that of female students was 60.0% in straight line equation material. So with that difference, it can be said that the mathematical communication ability of female students is higher than that of male students.